'Going with the flow' of dementia: A reply to Nigel Rapport on the social ethics of care. (21st June 2018) - Dawson, Andrew; Goodwin‐Hawkins, Bryonny
Abstract : In this editors' reply to Nigel Rapport's Afterword to the articles collected in the special issue 'Moralities of care in later life', we wonder: does the social ethics of care come with unacknowledged limits? We join with Rapport's call to maintain the individual's 'personal preserve' but observe—critically—that his "so far as possible, for as long as possible" makes for an uncomfortable caveat. To do so, we return ethnographically to the former mining town of Ashington, Northern England, and illustratively to a disease typically associated with the progressive loss of personhood: dementia. In contrast to both prevailing biomedical and person‐centred views of dementia, we adopt a radically relational approach, which in practice calls for attentiveness and opening oneself up on the part of the carer to the individual life‐world of another. Or, as it was for Ashington residents Eric and Elizabeth, a care‐full inter‐relationship re‐found in 'going with the flow'.